2013
DOI: 10.1038/mi.2013.2
|View full text |Cite
|
Sign up to set email alerts
|

Productive HIV-1 infection of human cervical tissue ex vivo is associated with the secretory phase of the menstrual cycle

Abstract: Cervical tissue explants (CTE) from 22 HIV-1 seronegative women were exposed to R5 HIV-1 ex vivo. Eight CTE were productively infected in terms of HIV-1 p24Gag release in culture supernatants whereas 14 were not. Nonetheless, both accumulation of HIV-1gag DNA and of p24Gag+ CD4+ T cells and macrophages occurred in both productive and, at lower levels, in nonproductive CTE. Nonproductive CTE differed from productive CTE for higher secretion of CCL3 and CCL5. A post-hoc analysis revealed that all productive CTE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 50 publications
3
73
1
2
Order By: Relevance
“…However, it is noteworthy that not all serine protease inhibitors we tested in this study (including SLPI and trappin-2) showed significantly different expression in the two menstrual phases. This is consistent with a recent ex vivo study (34) in which the authors showed no significant upregulation of ␤-defensins, SLPI, or proinflammatory cytokines in the follicular phase. However, they concluded that tissues from the luteal phase had a better capacity to support HIV-1 infection than those from the follicular phase, suggesting the presence of other innate factors in the follicular phase that might thwart infection.…”
Section: Discussionsupporting
confidence: 81%
“…However, it is noteworthy that not all serine protease inhibitors we tested in this study (including SLPI and trappin-2) showed significantly different expression in the two menstrual phases. This is consistent with a recent ex vivo study (34) in which the authors showed no significant upregulation of ␤-defensins, SLPI, or proinflammatory cytokines in the follicular phase. However, they concluded that tissues from the luteal phase had a better capacity to support HIV-1 infection than those from the follicular phase, suggesting the presence of other innate factors in the follicular phase that might thwart infection.…”
Section: Discussionsupporting
confidence: 81%
“…ϩ T cell population differences during the menstrual cycle with increased levels during menstruation (51), while others did not find increased CD4 ϩ T cell numbers in cervical explant tissues collected from the luteal phase or in progesterone-based contraceptive users (10,50). Although cell populations were not assessed in our study, our data suggested that neutrophil and CD4 ϩ T cell signatures were associated with the luteal phase by GSEA.…”
Section: Discussioncontrasting
confidence: 44%
“…Although still a topic of great debate there is a growing body of evidence that both endogenous and exogenous ovarian hormones, including estradiol and progesterone, are associated with increased HIV acquisition in women (3)(4)(5)(6)(7). Studies of nonhuman primates have shown that SHIV infection occurs more frequently during the progesteronedominant luteal phase of the menstrual cycle (8,9), and recent in vitro explant cultures of human cervical tissue have also shown that HIV infects explants collected during the luteal phase more productively than those collected during the follicular phase (10). Furthermore, progestins, which are synthetic progesterone derivatives commonly used in injectable hormonal contraceptives, have been shown to increase HIV acquisition risk by as much as 1.5-to 2.0-fold based on the latest meta-analysis (7,11).…”
mentioning
confidence: 99%
“…16 At the time coinciding with ovulation, Wira and colleagues have identified a potential 'window of vulnerability' during the progesterone-dominant luteal phase for optimal viral infection. 17,18 Through analysis of multiple immunologic parameters, they identified this 7-to 10-day 19 showed in a recent study utilizing cervical tissue explants that HIV infection was associated with the luteal phase. White and colleagues found that cytotoxic activity in the upper reproductive tract was present during the follicular phase of the cycle prior to ovulation, but was absent in the consequent luteal phase.…”
Section: Impact Of the Menstrual Cycle On Hiv Susceptibilitymentioning
confidence: 99%